The Effect of Innovation on the Performance of Small and Medium-Sized Enterprises Evidence from Pakistan - Irfan Ahmad Khan; Amir Hussain Shar; Mumtaz Ali Junejo (Review Journal of Social Psychology & Social Works, 2024)
The purpose of this research is to analyze the innovative capacity of SMEs in Islamabad, Pakistan. A total of 6,930 small and medium-sized enterprises (SMEs) in Islamabad were selected for the study. These businesses were granted licenses by the Pakistan Ministry of Trade and Investment and the Islamabad Local Government, respectively. A random sample of 375 SMEs was taken from this larger pool. To determine innovation's effect, the study employed descriptive and regression analysis. Regression analysis in the study reveals that innovation significantly affects the performance of SMEs in Islamabad. The study found that organizational, marketing, and product innovation had statistically significant effects on these SMEs.